Chronic Inflammatory Lameness Increases Cytokine Concentration in the Spinal Cord of Dairy Cows - Herzberg, Daniel; Strobel, Pablo; Ramirez-Reveco, Alfredo; Werner, Marianne; Bustamante, Hedie (Frontiers in Veterinary Science, 2020)
Lameness in dairy cows is an extremely painful multifactorial condition that affects the welfare of animals and economically impacts the dairy industry worldwide. The aim of this study was to determine the profile of cytokines in the spinal cord dorsal horn of dairy cows with painful chronic inflammatory lameness. Concentrations of 10 cytokines were measured in the spinal cord of seven adult dairy cows with chronic lameness and seven adult dairy cows with no lameness. In all cows lameness was evaluated using a mobility scoring system and registered accordingly. Immediately after euthanasia the spinal cord was removed and 20 cm of lumbar segments (L2-L5) were obtained. After dorsal horn removal and processing, cytokine quantification of tumor necrosis factor-alpha (TNF-α), interleukin-1alpha (IL-1α), interleukin 13 (IL-13), chemokine-10 (CXCL10/IP-10), chemokine-9 (CXCL9/MIG), interferon-alpha (IFN-α), interferon-gamma (IFN-γ), interleukin-21 (IL-21), interleukin-36ra (IL-36ra) and macrophage inflammatory protein-1 beta (MIP-1β) was performed using a multiplex array. Lame cows had higher concentrations of TNF-α, IL-1-α, IL-13, CXCL10, CXCL9, IFN-α and IFN-γ in their dorsal horn compared to non-lame cows, while IL-21 concentration was decreased. No differences in IL-36ra and MIP-1β concentrations between lame and non-lame cows were observed. Painful chronic inflammation of the hoof in dairy cows leads to a marked increase in cytokine concentration in the dorsal horn of the spinal cord, which could represent a state of neuroinflammation of the Central Nervous System (CNS).